2009
DOI: 10.1111/j.1600-0633.2009.00375.x
|View full text |Cite
|
Sign up to set email alerts
|

Movements of Murray cod (Maccullochella peelii peelii) in a large Australian lowland river

Abstract: This study of Murray cod (Maccullochella peelii peelii) movements in a large lowland river in south-eastern Australia indicated that the species was not sedentary, but undertook complex movements that followed a seasonal pattern. While there were sedentary periods with limited home ranges and high site fidelity, Murray cod also under took larger movements for considerable portions of the year coinciding with its spawning schedule. This generally comprised movements (up to 130 km) from a home location in late w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
113
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(121 citation statements)
references
References 49 publications
8
113
0
Order By: Relevance
“…Crook et al (2001) reported golden perch and carp to use habitats with similar water velocities during the day, but that golden perch used highervelocity areas at night. Nevertheless, the high levels of fidelity shown to these sites (Crook et al 2001;Koehn et al 2008Koehn et al , 2009 indicated their importance as home-habitat areas from which other local movements occur. The preference by trout cod for faster waters reflects the distribution of this species, which was once more widespread, particularly in higher-gradient upland streams (Trueman 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Crook et al (2001) reported golden perch and carp to use habitats with similar water velocities during the day, but that golden perch used highervelocity areas at night. Nevertheless, the high levels of fidelity shown to these sites (Crook et al 2001;Koehn et al 2008Koehn et al , 2009 indicated their importance as home-habitat areas from which other local movements occur. The preference by trout cod for faster waters reflects the distribution of this species, which was once more widespread, particularly in higher-gradient upland streams (Trueman 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Murray cod naturally occur in both faster-flowing, cooler, rocky, upstream river reaches and larger, turbid, slower-flowing lowland rivers, with an apparent preference for deep water and habitat with overhanging vegetation and in-stream woody habitat, the latter being important for shelter and spawning (Lintermans et al, 2005). The Murray cod is capable of large migratory and dispersal distances of up to 1500 km, but movements are typically limited to distances o200 km (Koehn et al, 2009). These movements are typically associated with upstream spawning migrations, with subsequent downstream larval drift, and Murray cod tend to exhibit strong site-fidelity outside of the spawning season (Koehn et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The Murray cod is capable of large migratory and dispersal distances of up to 1500 km, but movements are typically limited to distances o200 km (Koehn et al, 2009). These movements are typically associated with upstream spawning migrations, with subsequent downstream larval drift, and Murray cod tend to exhibit strong site-fidelity outside of the spawning season (Koehn et al, 2009). Spawning is temperature-cued, occurring in spring once temperatures reach 15°C (Koehn and Harrington, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For manual, mobile tracking, a portable receiver and antenna are used. Manual tracking of fish with radio transmitters can be performed by different means of transport such as by boat, foot, car, aircraft and horseback (Östergren and Rivinoja, 2008;Koehn et al, 2009;Gilroy et al, 2010). Manual tracking of fish with acoustic transmitters is best performed by boat since the hydrophone needs to be submerged in water.…”
Section: How To Record Fish Tagged With Radio and Acoustic Transmittersmentioning
confidence: 99%
“…The method is widely used in studies to increase the general knowledge of river migrations of freshwater and diadromous fishes (e.g. Almeida et al, 2002;Hodder et al, 2007;Koehn et al, 2009). It is also widely used to identify migration barriers and evaluate mitigation measures in rivers regulated for hydropower purposes, or impacted by other anthropogenic installations or regulations (e.g.…”
mentioning
confidence: 99%